1998
DOI: 10.1046/j.1365-2559.1998.00377.x
|View full text |Cite
|
Sign up to set email alerts
|

Autopsy findings in 27 children with haemophagocytic lymphohistiocytosis

Abstract: The diagnosis of HLH must be based on clinical, histological and additional laboratory findings. A negative bone marrow examination is common. Previous treatment with steroids and/or cytostatic drugs may attenuate or even eliminate the typical histological findings. Liver findings similar to those in chronic persistent hepatitis are common.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
47
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 130 publications
(50 citation statements)
references
References 12 publications
2
47
0
Order By: Relevance
“…Histologically, lymphocytes and mature macrophages exhibiting hemophagocytosis accumulate in numerous organs including spleen, liver, lymph nodes, bone marrow, and central nervous system (Ost, Nilsson-Ardnor, and Henter 1998). The clinical (Henter, Carlson, et al 1991) and hypofibrinogenemia results from fibrinolysis due to the release of plasminogen activator.…”
Section: Thrombocytopenia and Rbc Decreases Were Notmentioning
confidence: 99%
“…Histologically, lymphocytes and mature macrophages exhibiting hemophagocytosis accumulate in numerous organs including spleen, liver, lymph nodes, bone marrow, and central nervous system (Ost, Nilsson-Ardnor, and Henter 1998). The clinical (Henter, Carlson, et al 1991) and hypofibrinogenemia results from fibrinolysis due to the release of plasminogen activator.…”
Section: Thrombocytopenia and Rbc Decreases Were Notmentioning
confidence: 99%
“…4 A bone marrow examination is not required to establish the diagnosis, and autopsy findings of marrow hemophagocytosis are actually present in a minority of children at the time of death. 11 Classically, FHL manifests in the first few months of life, although rare cases have been reported with onset in adult years. 12 Three new diagnostic criteria have been added by the Histiocyte Society: (1) low or absent natural killer (NK) cell activity, (2) hyperferritinemia (ferritin X500 mg/l and (3) high plasma CD25 (IL-2 receptor) X2400 U/ml.…”
Section: Hemophagocytic Lymphohistiocytic Disordersmentioning
confidence: 99%
“…53,4,54 Autopsy evaluation study of the liver has shown chronic persistent hepatitis with periportal lymphocytic infiltration in 22 of 27 patients with HLH. 56 Our reported case had transaminitis. Hypertriglyceridemia, hypofibrinogenemia, elevated serum lactate dehydrogenase, hyponatremia are frequently seen in HLH.…”
Section: Discussionmentioning
confidence: 57%
“…As a result, if the bone marrow is not conclusive, material should be obtained from other organs e.g. ; liver, spleen, and lymph nodes 60,56 and occasionally the central nervous system , 61, 62 skin 63 and serial aspirates over time may also be helpful . 58,59 In our case, the bone marrow aspiration was performed and it revealed haemophagocytosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation